Effect of icosahedral phase on the thermal stability and ageing response of a duplex structured Mg–Li alloy. (15th March 2015) - Xu, D.K.; Wang, B.J.; Li, C.Q.; Zu, T.T.; Han, E.H.
Highlights: I-phase formation improves the thermal stability of the β-Li phase. Suppression of Li diffusion by I-phase causes age-hardening response of the α-Mg matrix. Age-softening response of the β-Li phase is due to the Li diffusion. Abstract: The formation of I-phase (Mg3 Zn6 Y, icosahedral structure) can suppress the lithium diffusion from β-Li (Mg solid solution in Li) to α-Mg (Li solid solution in Mg) and then remarkably improve the thermal stability of β-Li. Although the lithium diffusion is suppressed by I-phase pockets, quick precipitation and growth of MgLiZn particles can lead to the age-softening response of β-Li. However, a normal age-hardening response of α-Mg can be maintained. Thus, the macro hardness of the Mg–6%Li–6%Zn–1.2%Y alloy depends on the competition between the age-softening of β-Li and age-hardening of α-Mg.